The Effectiveness of Combination Therapy of Needling and Secretome from Mesenchymal Stem Cells (Serum 10%) for Acne Scar Treatment - Sukmawati Tansil Tan; Yohanes Firmansyah; William Gilbert Satyanegara; Edwin Destra; Giovanno Sebastian Yogie; Catharina Sagita Moniaga (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Acne scars can have various impacts on individuals, both physical and psychological. Acne scars arise as a result of complications from acne vulgaris. This study purposed to determine the effectiveness of the treatment using a combination of SC-PWJMSC with microneedling for acne scars. Methods: Pre-post clinical trial involving patients with acne scar. The intervention used in this study was a combination therapy of microneedling and secretome from mesenchymal stem cells. The intervention was carried out 1 time and monitored for 42 days. Primary outcome in the form of Observer visual scar assessment scale (OVSAS) was assessed at baseline and 42nd day, Secondary outcome (regenerative parameters) was assessed at baseline, 21st day and 42nd day. Results: There was a significant change in the primary and secondary outcomes (p-value <0.001) without any significant side effects. Conclusion: This study showed that combining needing with secretome from mesenchymal stem cells (MSCs) led to satisfactory results in repairing acne scars and in a number of other ways (secondary outcomes). On the other hand, there are limitations in this study in the form of no comparison therapy for the treatment of acne scar.